2014
DOI: 10.4149/bll_2014_043
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositid signal pathway mediate neurite outgrowth in PC12 cells by staurosporine

Abstract: Objectives:In previous studies, we showed that staurosporine uses intracellular calcium ions to affect cell death in PC12 cells. The bulk release of intracellular excessive Ca 2+ from intracellular sources into cytosol contributes to neuronal apoptotic events, which in turn results in neuronal cell death. However, the mechanisms of Ca 2+ -induced neuronal cell death or neurite elongation is still unclear. Therefore, we investigated the relation between phosphoinositid signal pathway, intracellular calcium, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
(33 reference statements)
1
2
0
Order By: Relevance
“…Recently, we reported that inhibition of IP3R and PLCγ led to attenuating of the rise in intracellular calcium triggered by staurosporine, thus strongly suggesting that ROS generation could potentiate the observed intracellular calcium overload (67). Our data showed that saturospurine at 1μM concentration induced cell death and reduced cell viability by increasing the NO secretion.…”
Section: +supporting
confidence: 47%
“…Recently, we reported that inhibition of IP3R and PLCγ led to attenuating of the rise in intracellular calcium triggered by staurosporine, thus strongly suggesting that ROS generation could potentiate the observed intracellular calcium overload (67). Our data showed that saturospurine at 1μM concentration induced cell death and reduced cell viability by increasing the NO secretion.…”
Section: +supporting
confidence: 47%
“…Cell culture conditions and the selection of the STS concentration were essentially performed according to Zhaleh et al studies (Zhaleh, Azadbakht, & Pour, 2011;Zhaleh, Azadbakht, & Pour, 2012;Zhaleh, Azadbakht, & Pour, 2014). The PC12 cells were cultured in RPMI-1640 culture medium (Gibco, Dublin, Ireland) in the presence of 1% NEAA (nonessential amino acid), and 1% antibiotic (penicillinstreptomycin, Sigma) in 25 ml tissue culture flasks.…”
Section: Cell Culture and Treatmentmentioning
confidence: 99%
“…However, apoptosis has also been observed under this condition. Measurement of total neurite length, the fraction of cell differentiation, and the percentages of apoptosis were reported in the previous works (Zhaleh et al, 2011(Zhaleh et al, , 2012(Zhaleh et al, , 2014.…”
Section: Sts Modifies the Cell Morphology Toward Neuron-like Phenotypesmentioning
confidence: 99%